Kedisiplinan Guru Pendidikan Agama Islam dalam Meningkatkan Hasil Belajar Siswa - Anggi Rivana; Musthofa Musthofa; Zubairi Zubairi; Siti Nur Ajizah (LP. Ma'arif Janggan Magetan, 2023)
Law on the National Education System No. 20 of 2003 states that, National education functions to develop abilities and shape the character and civilization of a dignified nation in order to educate the life of the nation, aiming to develop the potential of students to become human beings who believe and are devoted to God Almighty, noble character, physically and mentally healthy, knowledgeable, capable, creative, independent and a democratic and responsible citizen. However, at the implementation level, the government is not yet fully capable of producing quality human beings as stated in the national education goals above, in other words the educational process carried out still has many shortcomings. In this case the author raises the title of discipline of Islamic religious education teachers in improving student learning outcomes, because many people argue and assume that student learning success is only the responsibility of certain parties, even though student learning outcomes are not only influenced by the students themselves but also influenced by other factors. other things, and the discipline of teachers, especially Islamic religious education teachers, has a very large portion and responsibility because it concerns their capacity as educators who not only monitor from a cognitive perspective but also from an affective and psychomotor aspect without neglecting the role of teachers from other subjects. The author uses a research method with the type of Library Research research, namely by obtaining data sourced from books. The data that the author took through primary data and secondary data was collected by means of a literature review. Based on the results of research using Library Research, it is stated that there is relevance between teacher discipline and improving children's learning outcomes. That the teacher's attitude and attitude and discipline can encourage students to learn optimally. The purpose of this research is to motivate educators to improve guidance for students, with the results obtained from this research being able to increase insight and knowledge for the author in this case.